Types of Nonverbal Communication - Jiang, Xiaoming (IntechOpen, 2021)
The use of nonverbal cues in social activities is essential for human daily activities. Successful nonverbal communication relies on the acquisition of rules of using cues from body movement, eye contact, facial expression, tone of voice, and more. As such, this book adds to our understanding of nonverbal behavior by examining state-of-the-art research efforts in the field. The book addresses the classification and training of nonverbal communication with advanced technologies, gives an overview on factors underlying the learning and evaluating of nonverbal communications in educational settings and in digital worlds, and characterizes the latest advancement that uncovers the psychological nature underlying nonverbal communication in conversations. We hope the book will reach a large audience for a variety of purposes, including students and professors in academic institutions for teaching and research activities as well as researchers in industries for the development of communication-related products, benefiting both healthy individuals and special populations.